PEMBAGIAN WARISAN SAMA RATA (STUDI KONTEN BUYA YAHYA DI MEDIA SOSIAL YOUTUBE) - Yeni Mafiah; Muh. Zuhri (university Of islam, 2023)
The issue of inheritance distribution has often caused debate even since centuries before. This research aims to examine from the perspective of Islamic law the equal division of inheritance. The research method used is qualitative method with library research and content analysis approach. The result of the research is that basically Islam does not recognise an equal division of inheritance. And Islam has regulated in such detail the division of inheritance, as mentioned in the Quran and Hadith. The Quran is a holy book that is used as the main life guide for Muslims to be obeyed to get peace and peace in life. The Islamic inheritance system is very fair, and fair does not mean the same. Through the Al-Bahjah TV channel, Buya Yahya in his content explains that equal distribution of inheritance is also allowed under certain conditions, namely there must be no belief that the provisions for the distribution of inheritance that have been taught in the Al-Quran are unfair, then the next condition is that it is carried out voluntarily by the party with the larger share of inheritance. Buya Yahya emphasised the importance of following the rules of sharia and maintaining peace in the process of dividing inheritance. To minimise the risks of the world and the hereafter, if the inheritance will be distributed equally, then the settlement can also be done with other alternatives before the heir dies, namely by means of a grant contract or will contract. This research is expected to add broader insights regarding the distribution of inheritance equally.